THE EFFECT OF STEM INTEGRATED PROBLEM-BASED LEARNING MODEL (PBL) ON STUDENTS™ LEARNING OUTCOMES ON HUMAN RESPIRATORY AND EXCRETION SYSTEM - Ningtyas, Ratu Dwi; Sari, Monica Prima; Yanto, Febri; Lestari, Tuti (UNIVERSITAS NEGERI MEDAN, 2024)
Learning at UPT SMPN 1 Sutera seems to be still low, this is because the learning model used by teachers is still not appropriate and the discussion process has not been carried out well. One way to overcome this problem is to apply the STEM integrated Problem-Based Learning (PBL) model. This research aims to determine the effect of the STEM integrated Problem-Based Learning (PBL) model on student learning outcomes in human respiratory and excretory system material at UPT SMPN 1 Sutera. The type of research used in the research is Quasi Experiment, namely a research method to find the effect of certain treatments on others under controlled conditions. The design used in this research is the Non-Equivalent Control Group Design. The population in this study were class VIII students at UPT SMPN 1 Sutera. The sample in this study consisted of two classes, namely the experimental class and the control class which were taken using a purposive sampling technique. The instruments used consisted of an observation sheet on the implementation of the STEM integrated PBL model, pre-test and post-test questions. The research data obtained was then analyzed through descriptive statistical tests and inferential statistics using SPSS version 25. Based on the results of the analysis in hypothesis testing, it showed that there was a significant average difference between the control and experimental classes. The results of research hypothesis testing were found to be 0.000 and smaller than 0.05. Thus, it can be seen that the significant difference between Ha is accepted and H0 is rejected, so there is an influence. The conclusion from the hypothesis test is that there is a significant influence between students' scores using the STEM integrated PBL learning model. So H0 is rejected and Ha is accepted. So there is an influence of the STEM integrated PBL model on student learning outcomes.